Minimally invasive management of pyoperitoneum attributed by spontaneous perforated pyosalpinx and pyometra - Manisha, Polaki; Jeypal, Aparajita; Yerkade, Vasundhara; Devi, Hema; Mishra, Juhi; Khoiwal, Kavita; Chaturvedi, Jaya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Pyoperitoneum, apart from bowel perforation, can occur due to gynecologic causes like ruptured pyometra or ruptured tubo-ovarian abscess. Earlier, the management of pyoperitoneum included broad-spectrum antibiotics and emergency laparotomy with or without a hysterectomy and bilateral saphingo-oophorectomy. A higher rate of surgical complications like bowel or bladder injury was noted with surgery, and future fertility was also compromised in these patients. Later on, treatment strategies improved to laparoscopic drainage of pus with antibiotics without extensive surgery. However, such cases can be managed with an even more minimally invasive approach by image-guided pigtail drainage. In this report, we describe two cases of pyoperitoneum that were managed successfully with pigtail insertion and continuous drainage of pus along with antibiotics obviating the need for anaesthesia and surgery. It seems to be a promising approach for pyoperitoneum in a hemodynamically stable patient, not showing any features of severe sepsis.